A novel candidate therapeutic target for diabetic nephropathy: Gas6 - Erek, A.; Ozakpinar, O.; Karaca, Z.; Uras, F.; Uras, A. R. (My University)
Gastrointestinal stromal tumors (GISTs) are rare in the childhood period. The authors reported a case who was admitted to the neonatal intensive care unit (NICU) on a suspicion of intestinal obstruction. She was operated and a mass in a size of 6 xx 4.5 xx 4 cm was resected from the ileum. Histologic and immunohistochemical studies showed a GIST. CD34, small muscle actin (SMA), and desmin were positive. The baby was discharged on the 13th day after operation.</.